PERANCANGAN DATA WAREHOUSE AKADEMIK STMIK YADIKA BANGIL UNTUK PELAPORAN KINERJA PERGURUAN TINGGI - Panca Rahardiyanto (SPIRIT, 2020)
In compiling a Higher Education Performance Report in accordance with the regulations stipulated in Badan Akreditasi Nasional Regulation No.3 of 2019, it requires recapitulation or processing of historical data from higher education operational data. STMIK YADIKA BANGIL in compiling Higher Education Performance Reports currently does not have a centralized system that can be used to prepare data used in preparing Higher Education Performance Reports. In this research, a Data Warehouse that is centralized to store historical data starting in 2016 has been successfully designed and tested. With the Data Warehouse, data can be presented in accordance with its dimensions so that analysis can be carried out more efficiently and quickly to compile Higher Education Performance Reports at STMIK YADIKA BANGIL. The data presented is for reporting on new student selection, the adequacy of college lecturers, lecturer workload, research and PKM productivity, learning outcomes, student academic / non-academic achievement, educational effectiveness and productivity, competitiveness of graduates, graduate performance, and scientific publications.Keywords : data warehouse, higher education, performance report